Pull-Down Into Active Inclusion Bodies and Their Application in the Detection of (Poly)-Phosphates and Metal-Ions - Hrabarova, Eva; Belkova, Martina; Koszagova, Romana; Nahalka, Jozef (Frontiers in Bioengineering and Biotechnology, 2022)
Inclusion bodies are typically ignored as they are considered unwanted protein waste generated by prokaryotic host cells during recombinant protein production or harmful protein inclusions in human cell biology. However, these protein particles may have applications for in vivo immobilization in industrial biocatalysis or as cell-tolerable protein materials for the pharmaceuticals industry and clinical development. Thus, there is a need to “pull-down” soluble enzymes and proteins into inclusion bodies. Accordingly, in this study, sequences from the short-chain polyphosphatase ygiF were used to design pull-down tags capable of detecting (poly)-phosphates and metal ions. These tags were compared with the entire CHAD domain from Escherichia coli ygiF and SACS2 CHAD from Saccharolobus solfataricus. The results demonstrated that highly soluble green fluorescent protein variants could be pulled down into the inclusion bodies and could have modified sensitivity to metals and di-/tri-inorganic phosphates.